Deciphering colorectal cancer immune microenvironment transcriptional landscape on single cell resolution – A role for immunotherapy - Tieng, Francis Yew Fu; Lee, Learn-Han; Ab Mutalib, Nurul-Syakima (Frontiers in Immunology, 2022)
Single cell RNA sequencing (scRNA-seq) is a novel high-throughput technique that enables the investigation of a single cell's entire transcriptome. It elucidates intricate cellular networks and generates indices that will eventually enable the development of more targeted and personalised medications. The importance of scRNA-seq has been highlighted in complex biological systems such as cancer and the immune system, which exhibit significant cellular heterogeneity. Colorectal cancer (CRC) is the third most common type of cancer and the second leading cause of cancer-related death globally. Chemotherapy continues to be used to treat these patients. However, 5-FU has been utilised in chemotherapy regimens with oxaliplatin and irinotecan since the 1960s and is still used today. Additionally, chemotherapy-resistant metastatic CRCs with poor prognoses have been treated with immunotherapy employing monoclonal antibodies, immune checkpoint inhibitors, adoptive cell therapy and cancer vaccines. Personalized immunotherapy employing tumour-specific neoantigens allows for treating each patient as a distinct group. Sequencing and multi-omics approaches have helped us identify patients more precisely in the last decade. The introduction of modern methods and neoantigen-based immunotherapy may usher in a new era in treating CRC. The unmet goal is to better understand the cellular and molecular mechanisms that contribute to CRC pathogenesis and resistance to treatment, identify novel therapeutic targets, and make more stratified and informed treatment decisions using single cell approaches. This review summarises current scRNA-seq utilisation in CRC research, examining its potential utility in the development of precision immunotherapy for CRC.